Helicobacter pylori infection in diabetes mellitus patients with peptic ulcer disease (IMC Journal of Medical Science, 2021)
Background and objectives: Helicobacter pylori infection is suspected to be associated with extra-gastrointestinal disorders such as diabetes mellitus (DM). It is still a subject of investigation whether H. pylori has a pathogenic role on DM or diabetic patients have an increased susceptibility to H. pylori infection. The aim of the present study was to find out the rate of H. pylori infection in individuals with and without DM.Materials and methods: The study was conducted on 72 diabetic and 19 non-diabetic adult individuals with dyspeptic symptoms attending the BIRDEM General Hospital for diagnostic endoscopy. All cases were tested for H. pylori stool antigen by rapid immunochromatographic test (ICT), urease production in biopsy samples by rapid urease test (RUT), and serum anti-H. pylori IgA and anti-CagA IgG antibodies by enzyme-linked immunosorbent assay (ELISA). Any case that had peptic ulcer/erosion and was positive for H. pylori stool antigen or rapid urease test (RUT) was defined as H. pylori positive case.Results: There was no significant (p=0.095) difference in H. pylori infection between diabetics and non-diabetics (68.1% vs 47.4%). Presence of ulcer and erosion were not significantly different among diabetics and non-diabetics. Anti-H. pylori IgA positivity rate in H. pylori positive diabetic and non-diabetic cases were 65.3% and 55.6% (p=0.575) respectively while anti-CagA IgG rate in those cases were 46.9% and 66.7% (p=0.276) respectively.Conclusion: The present study did not reveal any significant difference in H. pylori infection between individuals with and without DM having peptic ulcer/erosion.Ibrahim Med. Coll. J. 2020; 14(2): 27-32